Capability Readiness for Product-Service Systems - Tetlay, Abideen; John, Philip (Cranfield University, 2009)
This article discusses the relationship between “Capability”and „Product-Service Systems‟(PSS) and the need for the assessment of „Capability Readiness‟(CR) for PSS. It is suggested that this assessment is essential to determine whether or not the elements of capability for PSS are in place and maintained for the successful delivery of a sustainable PSS.
Keywords: Capability; Capability Readiness; Product-Service Systems; System Readiness; System Maturity